A sex dependent association between the history of autoimmune disease and the development of pancreatic cancer: a case-control study of 32,640 patients - Loosen, Sven H.; Hansen, Frederik J.; Luedde, Tom; Roderburg, Christoph; Kostev, Karel (Frontiers in Oncology, 2025)
BackgroundPancreatic cancer is a highly lethal cancer with increasing incidence and poor prognosis due to late diagnosis. While several risk factors are known, evidence on a potential role of autoimmune diseases remains limited. Given the increasing prevalence of autoimmune diseases and their association with various malignancies, this study aims to investigate their potential association with pancreatic cancer.Methods5,440 patients with a first diagnosis of pancreatic cancer and 27,200 propensity score matched individuals without cancer were identified from the Disease Analyzer database (IQVIA). The outcome of the study was the association between the diagnosis of pancreatic cancer and a patient´s history of autoimmune disease.ResultsInflammatory bowel disease (OR: 1.69; 95% CI: 1.34-2.12) and rheumatoid arthritis (OR: 1.20; 95% CI: 1.03-1.41) were significantly associated with increased odds of pancreatic cancer. The OR was 1.25 for systemic lupus erythematosus and 1.26 for multiple sclerosis without reaching a statistical significance. In sex-stratified analyses, inflammatory bowel disease was strongly associated with pancreatic cancer in women (OR: 2.14; 95% CI: 1.59-2.89) but not in men (OR: 1.24; 95% CI: 0.86-1.78). A positive association between rheumatoid arthritis and pancreatic cancer was also observed in women (OR: 1.26; 95% CI: 1.03-1.53) but not in men (OR: 1.09; 95% CI: 1.03-1.53-1.44). In addition, the ORs for SLE (1.82) and MS (1.45) were increased in women to a clinically relevant extent that did not reach the significance level of <0.05. A similar increase was not observed in male patients.ConclusionAutoimmune disease may be associated with an increased risk of developing pancreatic cancer, particularly in women. This highlights the importance of addressing gender differences in medical practice, particularly in relation to disease screening and surveillance.